2014
DOI: 10.1148/radiol.14132872
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Small-Bowel Obstruction: Value of CT in Identifying Findings Associated with the Effectiveness of Nonsurgical Treatment

Abstract: The number of beak signs and the location of the transition zone in relation to the anterior peritoneal layer are independent signs associated with the success or failure of nonsurgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 26 publications
0
52
1
3
Order By: Relevance
“…Furthermore, it has been suggested that the oral administration of a small amount of Gastrografin can lead to the resolution of ASBO [2][3][4][5][6][7][8][9][10].…”
Section: Radiologic Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been suggested that the oral administration of a small amount of Gastrografin can lead to the resolution of ASBO [2][3][4][5][6][7][8][9][10].…”
Section: Radiologic Diagnosismentioning
confidence: 99%
“…A double-contrast CT scan is the imaging procedure of choice because of its high sensitivity and specificity in the diagnosis of ischemia and degree of obstruction (partial vs complete) [3][4][5][6][7][8][9][10][11][12]. It can be helpful to determine the etiology of obstruction, such as internal or abdominal wall hernias, intussusception, tumor or mass, Crohn's disease, metastatic cancer, ischemia, and sign of intestinal compromise such as pneumatosis intestinalis or pneumoperitoneum.…”
Section: Radiologic Diagnosismentioning
confidence: 99%
“…In a closed loop obstruction, 2 transition point beak signs may be seen. The absence of a 'beak sign' is associated with successful non-operative management in the setting of adhesion related SBO, along with the presence of a small bowel feces sign and an anterior parietal adhesion 59 . On the other hand, two 'beak signs' or more, a whirl sign, a C-or U-shaped bowel loop and highgrade obstruction are more likely to require surgical management in the setting of adhesional SBO 59,60 .…”
Section: Transition Point 'Beak Sign'mentioning
confidence: 99%
“…Complete obstruction on the other hand is the opposite of these entities. High-grade obstruction is more likely to require operative management in the setting of adhesion related SBO 59 .…”
Section: Gradingmentioning
confidence: 99%
See 1 more Smart Citation